Research Trend Bi-Model Media in Science Education: Bibliometric Analysis - Andari, Kadek Dewi Wahyuni; Suhandi, Andi; Sa’ud, Udin Syaefusin; Kaniawati, Ida (International Conference on Elementary Education, 2025)
This study analyzes the global development and research trends of bi-model media in science education using a bibliometric approach. Data from the Scopus database were processed with Biblioshiny and VOSviewer to identify the conceptual structure, thematic clusters, and emerging directions. The results show that e-learning, virtual reality, and students are dominant themes driving a shift toward interactive and learner-centered education, while artificial intelligence, machine learning, and social media form the foundation for developing data-driven adaptive learning systems. The thematic and keyword network analyses indicate a growing transition toward a hybrid framework that integrates technology, pedagogy, and human experience. The findings highlight the importance of aligning pedagogical design with intelligent technological support to create meaningful, adaptive, and context-based learning experiences. Although limited to a single bibliographic source, this study contributessignificantly to mapping the research landscape of bi-model media and offers insights for future studies on AI-based integration, learning analytics, and equitable access to digital education in the 21st century. Unlike previous bibliometric studies that broadly examine digital or technology-enhanced learning, this work uniquely foregrounds the emerging concept of bi-model media, providing a sharper lens to understand how dual-mode representations shape scientific understanding and instructional innovation.